2021
DOI: 10.1007/s10143-021-01657-4
|View full text |Cite|
|
Sign up to set email alerts
|

Post-traumatic intracranial pseudo-aneurysms of posterior circulation: a comprehensive review of an under-diagnosed and rare entity

Abstract: Traumatic aneurysms are rare and the total number of cases involving the posterior circulation (TIPC) is even smaller. Traumatic brain injury (TBI) may be responsible not only of rupture in brain aneurysm (BrA) pre-existing to trauma, but it has been identified also as a possible pathogenetic cause of TIPC formation in patients not affected by intracranial vascular lesions. A complete literature review was performed of all reported cases regarding rupture of BrA with SAH resulting from TIPC not previously iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…As it is well known, even a slight rotational trauma could have led to the formation and rupture of aneurysms [3,11,14]. Performing CT angiography and Digital Subtraction Angiography (DSA) a few hours after the attack not only has a diagnostic-therapeutic role, but can be useful tool to carry out medico-legal assessment [15]. Histological investigations are a further tool to clarify the nature of the aneurysm [16].…”
Section: Discussionmentioning
confidence: 99%
“…As it is well known, even a slight rotational trauma could have led to the formation and rupture of aneurysms [3,11,14]. Performing CT angiography and Digital Subtraction Angiography (DSA) a few hours after the attack not only has a diagnostic-therapeutic role, but can be useful tool to carry out medico-legal assessment [15]. Histological investigations are a further tool to clarify the nature of the aneurysm [16].…”
Section: Discussionmentioning
confidence: 99%
“…The rupture time of intracranial aneurysms often varies greatly, mostly 2 to 3 weeks after trauma, and the mortality rate often exceeds 50%. [7] Therefore, timely diagnosis and treatment before aneurysm rupture are very important. [8] CTA or cerebral angiography should be performed immediately after the injury, and CTA or digital subtraction angiography should be reviewed within the next few days.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the English and Japanese language literature performed on December 3, 2021, revealed 12 reports describing 15 cases of PICA-TICA. [1,2,5,8,9,12,[14][15][16][17] e clinical characteristics and outcomes of these patients are summarized in Table 1. Among the 15 cases (including our patient), the mean patient age was 32.4 (15-69) years.…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] Endovascular treatment was performed in five of the previously reported 20 cases of PICA-TICA. [5,14] is case report outlines the steps taken to treat the PICA-TICA, patient outcomes, and lessons learned for effective treatment of future PICA-TICA patients. We also reviewed previous reports on the characteristics and treatment of PICA-TICA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation